2022
DOI: 10.1038/s41467-022-28566-4
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative molecular and clinical profiling of acral melanoma links focal amplification of 22q11.21 to metastasis

Abstract: Acral melanoma, the most common melanoma subtype among non-White individuals, is associated with poor prognosis. However, its key molecular drivers remain obscure. Here, we perform integrative genomic and clinical profiling of acral melanomas from 104 patients treated in North America (n = 37) or China (n = 67). We find that recurrent, late-arising focal amplifications of cytoband 22q11.21 are a leading determinant of inferior survival, strongly associated with metastasis, and linked to downregulation of immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 119 publications
2
36
0
Order By: Relevance
“…There were 32 regions specifically amplificated or deleted in HAS ( Figure S7C,D ), and the amplification of chr22q11.21 and deletions of chr1p36.21, chr7q11.21, chr7q22.1, chr9q12 as well as chr12q24.33 predicted a tendency of shorter OS. Intriguingly, Farshidfar et al demonstrated that chr22q11.21 amplification in melanoma was strongly associated with inferior survival, metastasis, and downregulation of immunotherapy response-related genes [ 38 ], indicating its important role in HAS. Additionally, chr10q21.2 amplification was linked with precursor B-cell acute lymphoblastic leukemia of childhood [ 39 ], and in this study we found it was associated with local vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…There were 32 regions specifically amplificated or deleted in HAS ( Figure S7C,D ), and the amplification of chr22q11.21 and deletions of chr1p36.21, chr7q11.21, chr7q22.1, chr9q12 as well as chr12q24.33 predicted a tendency of shorter OS. Intriguingly, Farshidfar et al demonstrated that chr22q11.21 amplification in melanoma was strongly associated with inferior survival, metastasis, and downregulation of immunotherapy response-related genes [ 38 ], indicating its important role in HAS. Additionally, chr10q21.2 amplification was linked with precursor B-cell acute lymphoblastic leukemia of childhood [ 39 ], and in this study we found it was associated with local vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a 22q11.21 focal amplification is found in 10% of the CCLE skin cancer cell lines (e.g. Hs294-T and COLO679 BRAF(V600) mutant cell lines), 22q11.21 was also identified as recurrently amplified in a pan-cancer analysis (Zack et al, 2013), and was recently associated with inferior survival in acral melanoma (Farshidfar et al, 2022). Subclonal differences in the presence, size and copy number were observed for the majority of the focal amplifications on chr13 (Fig.…”
Section: Detection Of Subclone-specific Focal Amplifications At Near ...mentioning
confidence: 99%
“…Farshidfar et al have found that recurrent, late-arising focal amplifications of cytoband 22q11.21 associated with limbic melanoma metastasis was a major determinant of poor clinical outcome and was related to the downregulation of immunomodulatory genes associated with immunotherapeutic response. For example, LZTR1 and CRKL are two important genes associated with 22q11.21 amplification in limbic melanoma, and LZTR1 can be a viable therapeutic target [ 64 ].…”
Section: Mutational Landscapementioning
confidence: 99%
“…For example, a study has previously determined mutations associated with AM invasion and metastasis, including EP300, ANO1, CPEB1, INADL, MAP1B, MAP7D1, MARCH 6, NETO1, PRKCE, SBK1, TNRC6A, USP13, WDR74, and ZNF827 [63] of poor clinical outcome and was related to the downregulation of immunomodulatory genes associated with immunotherapeutic response. For example, LZTR1 and CRKL are two important genes associated with 22q11.21 amplification in limbic melanoma, and LZTR1 can be a viable therapeutic target [64].…”
Section: Mutational Landscapementioning
confidence: 99%